2012
DOI: 10.3390/nu4121851
|View full text |Cite
|
Sign up to set email alerts
|

Dose and Latency Effects of Leucine Supplementation in Modulating Glucose Homeostasis: Opposite Effects in Healthy and Glucocorticoid-Induced Insulin-Resistance States

Abstract: Dexamethasone (DEXA) is a potent immunosupressant and anti-inflammatory agent whose main side effects are muscle atrophy and insulin resistance in skeletal muscles. In this context, leucine supplementation may represent a way to limit the DEXA side effects. In this study, we have investigated the effects of a low and a high dose of leucine supplementation (via a bolus) on glucose homeostasis, muscle mass and muscle strength in energy-restricted and DEXA-treated rats. Since the leucine response may also be link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…Contrary to our findings, Zanchi et al. () showed that a diet supplemented with leucine impaired motor performance in mice with muscular atrophy induced by dexamethasone.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our findings, Zanchi et al. () showed that a diet supplemented with leucine impaired motor performance in mice with muscular atrophy induced by dexamethasone.…”
Section: Discussioncontrasting
confidence: 99%
“…These data suggest that in diabetic animals, the anabolic effects of leucine depend on the mechanical stimulus of resistance training, unlike what occurs in healthy subjects (Zanchi et al. ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Conversely, leucine deprivation elevates phosphorylated levels of IGFBP-1, which in turn suppresses IGF-I-stimulated cell proliferation and hence results in fetal growth restriction [80]. Low-dose leucine supplementation exerts positive effects, including improved insulin sensitivity in the whole body [81]. Intriguingly, dietary supplementation with leucine to rats born from obese dams can promote fat oxidation and glucose transport in peripheral tissues, and, therefore, can ameliorate metabolic disorders [82].…”
Section: Nutritional Intervention With Amino Acids In Metabolic Syndromementioning
confidence: 97%
“…While a number of studies demonstrate that either amino acid mixture or BCAA supplementation have beneficial effects on protein turnover and muscle wasting in patients with cirrhosis, kidney failure, cancer, or sepsis, [14][15][16][17][18][19][20][21][22][23][24][25] mounting evidence suggests that amino acids/BCAAs or their metabolized keto acids lead to hyperactivation of mTOR signaling, 7,26-28 induction of oxidative stress, 29-32 mitochondrial dysfunction, 33,34 apoptosis, 35,36 and more importantly, insulin resistance and/or impaired glucose metabolism. 7,[26][27][28][37][38][39][40][41][42][43][44] Consistent with these findings, recent studies demonstrate that a BCAA metabolite elevated in diabetic individuals can drive vascular fatty acid transport in muscle and induce insulin resistance in mice 44 and a defective muscle BCAA metabolism induces impaired lipid metabolism and insulin resistance.45 On the other hand, deprivation of a single or all three BCAAs improves insulin sensitivity and glycemic control in either chow-or High-Fat Diet (HFD)-fed, or genetically diabetic rodents.46-48 These findings strongly indicate not only a correlative, but also a causative role of circulating BCAAs and their oxidized intermediates in the development of insulin resistance and diabetes. As such, it is important to advance our understanding of BCAA regulatory mechanisms that would allow us to explain the reasons for high circulating levels of BCAAs found in obese and diabetic individuals.…”
mentioning
confidence: 99%